The ticking tail: daily oscillations in mRNA poly(A) tail length drive circadian cycles in protein synthesis - Gotic, Ivana (Cold Spring Harbor Laboratory Press, 2012)
In this issue of Genes & Development, Kojima and colleagues (pp. 2724–2736) examined the impact of mRNA poly(A) tail length on circadian gene expression. Their study demonstrates how dynamic changes in transcript poly(A) tail length can lead to rhythmic protein expression, irrespective of whether mRNA accumulation is circadian or constitutive.